Modeling Musculoskeletal Disorders in Zebrafish: Advancements in Muscle and Bone Research - Luca Dalle Carbonare; Michele Braggio; Arianna Minoia; Mattia Cominacini; Maria Grazia Romanelli; João Pessoa; Natascia Tiso; Maria Teresa Valenti (Cells)
Zebrafish (Danio rerio) have emerged as a valuable model organism for investigating musculoskeletal development and the pathophysiology of associated diseases. Key genes and biological processes in zebrafish that closely mirror those in humans, rapid development, and transparent embryos make zebrafish ideal for the in vivo studies of bone and muscle formation, as well as the molecular mechanisms underlying musculoskeletal disorders. This review focuses on the utility of zebrafish in modeling various musculoskeletal conditions, with an emphasis on bone diseases such as osteoporosis and osteogenesis imperfecta, as well as muscle disorders like Duchenne muscular dystrophy. These models have provided significant insights into the molecular pathways involved in these diseases, helping to identify the key genetic and biochemical factors that contribute to their progression. These findings have also advanced our understanding of disease mechanisms and facilitated the development of potential therapeutic strategies for musculoskeletal disorders.